Aktivitas Antibakteri Ekstrak Metanol Buah Mbosi (Dysoxylum gaudichandianum (A.Juss) Miq.) dan Penapisan Senyawa Kimianya - Praptiwi Praptiwi; Mindarti Harapini (Universitas Atma Jaya Yogyakarta, 2005)
Mbosi (Dysoxylum gaudichandianum (A.Juss) Miq.) belongs to Meliaceae family, Its potential bioactivity had not been known although the other plants from the same family had been known as natural insectiside or medicinal plants. Phytochemical screening showed that mbosi fruit contained fat, fatty acid, sterol, triterpenoide, tannin, peroxide sugar, alkaloid, steroid glycoside and flavonoid. Identification of mbosi fruit chemical compounds by GC-MS showed that it contained 16 compounds. Compounds with the concentration more than 5 % were butyl cellosolve (11.1%), erythritol (8.48%), glycerol (10.32%), hexadecanioc acid palmitinic ester (16.2%), oleic acid (65.3%) and ethyl oleat (6.2%). In-vitro antibacterial test on innoculated Mueller Hinton Agar to seven bacteria isolates (Salmonella typhimurium, S. typhii, Eschechiria coli ATCC 25923, Pseudomonas sp., Staphylococcus aureus ATCC 25922, S. epidermidis, and Bacilus subtilis) showed that 20% methanol extract inhibit only the growth of Staphylococcus aureus.